Productive And Consumptive Zakat Among The Mustahik-Owned Super-Micro Businesses During The Covid-19 Pandemic Period: A Qualitative Approach - T, T. Saipul Hadi; Bintang Aulia Lutfi; Mohamad Rifqi Fathoni (IAIN Langsa, 2023)
Zakat serves as a crucial instrument for wealth redistribution aimed at reducing social inequality, particularly amidst the impacts of the COVID-19 pandemic. The implementation of zakat is imperative to stimulate significant contributions to both productive and consumptive zakat distributions. This research endeavors to delineate and chart the proportional distribution of productive and consumptive zakat to super-micro business mustahiks during the COVID-19 pandemic. Employing a qualitative approach involving literature review and in-depth interviews, this study aims to achieve a comprehensive understanding and mapping of mustahik. The study revealed that consumptive zakat is earmarked for mustahiks falling within the faqir category among the eight asnaf. Conversely, productive zakat is allocated to mustahiks classified as poor within the eight asnaf, prioritizing those who already possess a business, demonstrate expertise in specific fields, and hold a market share. The implication of this research underscores that by meticulously mapping and allocating zakat according to the needs and categories of mustahik, Islamic Social Finance (ISF) institutions can provide suitable assistance aligned with the economic conditions of the recipients. To ensure equitable and targeted distribution of productive and consumptive zakat, it is imperative to bolster public comprehension of zakat, conduct outreach regarding the distribution process, and develop an efficient mapping system.